Effect of different types and levels of errors in sire pedigree on the accuracy of genetic evaluation in crossbred goats - Tesema, Z.; Deribe, B.; Tilahun, M.; Lakew, M.; Getachew, T.; Gizaw, Solomon (Elsevier, 2023)
The effects of different types and levels of errors in sire pedigree on genetic variance, heritability, inbreeding coefficient, estimated breeding value, the accuracy of breeding value and the genetic trend were evaluated. The proportion of interchanged sire (SIC) and progenies without sire (PWS) was varied in four steps from 25 to 100%. These eight pedigree files were compared to a pedigree file with complete pedigree information (CPI). The WOMBAT program fitting animal model was used to determine genetic parameters. The correlations among estimated breeding values (EBV) and between rank of animals resulted from different pedigree files were estimated using using the Pearson correlation and Spearman rank correlation procedure of SAS, respectively. Except for 25–50%PWS, all pedigree files with sire pedigree error overestimated the direct additive genetic variance (σ2a) and direct heritability (h2a) compared to a pedigree file with CPI. The error in sire pedigree underestimated EBV, the accuracy of EBV, and affect the rank of kids. The correlation estimate reduces with an increase of proportion of PWS and was similar for pedigree files with SIC. The magnitude of genetic reduction per year was lower for pedigree files with sire pedigree error compared to pedigree file with CPI. The mean inbreeding coefficient decreased (0.321–0.00%) with increasing the proportion of PWS. Pedigree files with sire pedigree error overestimate the direct heritability, total heritability, EBV, reduce the accuracy of EBV, bias the genetic trend and underestimate the inbreeding level in the flock. However, the genetic parameter estimates derived from the pedigree files with SIC were nears to estimates from the pedigree file with CPI. Improving the recording system and awareness creation about its impact is imperative for a successful genetic improvement program and accurate genetic evaluation.